Androgen-producing bilateral large cortical adrenal adenomas associated with polycystic ovaries in a young female. Issue 797 (March 1992) - Micić, D.; Zorić, S.; Popović, V.; Janković, R.; Jancić, M.; Han, R.; Manojlović, D.; Mićić, J.
Abstract : An association of bilateral large adrenocortical androgen-producing adenomas with polycystic ovaries in a young female is presented. She developed mild hirsutism and secondary amenorrhoea at the age of 17, and was treated for 3 years with an anti-androgen (cyproterone acetate) and ethinyloestradiol. Routine follow-up at the age of 21 showed bilateral large adrenal tumours and polycystic ovaries, together with high serum testosterone and dehydroepiandrosterone sulphate values. Bilateral adrenalectomy was performed, which resulted in lowering of the elevated androgens, and large bilateral adrenocortical adenomas were confirmed histologically. Contrary to expectations, the polycystic appearance of the ovaries persisted after adrenalectomy. This case supports the possible role of adrenal androgens in the pathogenesis of polycystic ovaries as well as the possibility of the persistence of polycystic ovaries without adrenal androgens once they have developed.